(3JcfhdhLjG GdJMQQ (B:s (3hSGFd GdEYdGe GdGLJeGYj h GdcaGM aj SHjd GdOjebQGWjI (B/s - (3dGQj OGjehfO s; (3eGQc HdGJfQs ((3GdGeGQGJ (B:s (3eQcR GdEeGQGJ ddOQGSGJ h GdHMhK GdGSJQGJjLjI ,s, 2013)
(3jLeY cJGH JcfhdhLjG GdJMQQ NHQGJ eJbOeI ef HGMKjf h YGedjf aj gPG GdeLGd h gh jHOG HebOeI JMOO GdfbGT h JbOe eYdheGJ GSGSjI Yf JcfhdhLjG GdJMQQ JJHYgG aUhd JfGbT KfGFjI GdJMQQ ebGHd GdJMce ajeG jJYdb HGdGfJQfJ h GdGHYGO GdGLJeGYjI h GdSjGSjI dgPG GdJMce h gfGc aUhd GVGajI jJfGhd cd efgG GdhVY aj GMO GdHdOGf GdJGdjI GdUjf h eUQ h GjQGf h JhfSs
(3HHdjhZQGajG (B: (3U(B.291-320s
Keywords: (3GdOjebQGWjIs; (3hSGFd GdEYdGe GdELJeGYjs; (3JcfhdhLjGs